The Effect of Managed Care on Hospitals' Provision of Uncompensated Care - Niccie L. McKay; Xiaoxian Meng (SAGE Publishing, 2007)
This study examines the effect of managed care on hospitals' provision of uncompensated care, using a new measure of managed care that is hospital-specific, rather than measured for the area as a whole, and which includes payment by preferred provider organizations (PPOs) as well as by health maintenance organizations (HMOs). Based on data for Florida hospitals in the period 1998-2002, the results indicate that a higher percentage of private managed care patient-days was associated with a decrease in uncompensated care as a percentage of total operating expenses, holding net profit margin and other factors constant. The results suggest that spillover effects on uncompensated care should be taken into account when considering increases in managed care payment.